Genetic Ancestry Is Associated With Measures of Subclinical Atherosclerosis in African Americans: The Jackson Heart Study. Issue 5 (May 2015) - Gebreab, Samson Y.; Riestra, Pia; Khan, Rumana J.; Xu, Ruihua; Musani, Solomon K.; Tekola-Ayele, Fasil; Correa, Adolfo; Wilson, James G.; Rotimi, Charles N.; Davis, Sharon K.
Abstract : Objective—: To determine whether genetic ancestry was associated with subclinical atherosclerosis measures after adjustment for traditional cardiovascular disease risk factors, inflammatory marker, socioeconomic status, and psychosocial factors in a large admixed African American population. Approach and Results—: Participants were drawn from the Jackson Heart Study. Participant's percent of European ancestry (PEA) was estimated based on 1747 genetic markers using HAPMIX. Association of PEA with peripheral arterial disease and common carotid intima-media thickness were investigated among 2168 participants and with coronary artery calcification >0 and abdominal aortic calcification >0 among 1139 participants. The associations were evaluated using multivariable regression models. Our results showed that a 1 SD increase in PEA was associated with a lower peripheral arterial disease prevalence after adjusting for age and sex (prevalence ratio=0.90 [95% CI, 0.82–0.99]; P =0.036). Adjustments for traditional cardiovascular disease risk factors, socioeconomic status, and psychosocial factors attenuated this association (prevalence ratio=0.91 [0.82–1.00]; P =0.046). There was also a nonlinear association between PEA and coronary artery calcification and abdominal aortic calcification. The lowest PEA was associated with a lower coronary artery calcification (prevalence ratio=0.75 [0.58–0.96]; P =0.022) and a lower abdominal aortic calcification [prevalence ratio=0.80 [0.67–0.96]; P =0.016) compared with the reference group (10th–90th percentile) after adjusting for traditional cardiovascular disease risk factors, inflammatory marker, socioeconomic status, and psychosocial factors. However, we found no significant association between PEA and common carotid intima-media thickness. Conclusions—: Overall, our findings indicate that genetic ancestry was associated with subclinical atherosclerosis, suggesting unmeasured risk factors and interactions with genetic factors might contribute to the distribution of subclinical atherosclerosis among African Americans. Abstract : Supplemental Digital Content is available in the text.